Waste oil-based paint as additive in stone mastic asphalt - Cheong, Sin Soon (2013)
Thecost of asphalt is crucial in determining the cost of construction in the year 2008, the averaage price of Malaysian crudes is more than 100 USD per barrel. AS a result a hike in the price of asphalt is observed within the same year. Studies on replace asphalt as binder or reduce the amount of asphalt used should be carried out to reduce the construction cost. In the other hand, thre is more than 15000 metric tonnes of ink and paint sludge generated yearly since the year 2006. the waste oil-based paint was chosen to blend with asphalt since it was better bonding when mixed together. Three tpes of brinders i.e 80/100 penetration graded asphalts, 60/70 penetration graded asphalt and performance grade PG.76 were used to blend with waste oil-base paint.m The amount of waste paint used in the blending with asphalt binder were 5%, 10% and 20% of the total weight. The physical test on asphalt were carried out in accordance with ASTM standards. The maximun amount of waste paint blended into these three binders that met the minimum requirement of PWD standard were chosen . It was found that the 80/100 penetration graded asphalt blended with 10% of water paint and the PG 76 blended with 20% of waste paint met the minimum requirement of the PWD standard. SMA was used in this study. It is not mixture asphalt consisting of a coarse aggregate skeleton and a high binder content mortar. The performance tests such as Resilient Modulus, moisture susceptibility and permanent deformation tests were carried out on the paint modified asphalt binder specimens. These results were compared with the samples that used original binder as control. It was found that asphalts mixtures However they still met the requirements of the PWD standard. Therefore waste oil-based paint can be used to replace 5% of 80/100 penetration graded asphalt. 10% of 60/70 penetration graded asphalt and 20% of PG 76 used in road construction. The length of PLUSS highways is 772 km. Assume that PLUSS highway undergo rehabilitation yearly with overlay thickness of 50 mm, the cost of asphalt for rehabilitation (one lane per km) can be saved up to RM 902.50 if 80/100 -penetration graded asphalt is used RM6,136.50 if 60/70 penetration graded asphalt is used and RM25,258.50 if performance grade, PG is used.